2020
DOI: 10.34133/2020/3729715
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Multiview Imaging for Estimating Seedling Tiller Counts of Wheat Genotypes Using Drones

Abstract: Early generation breeding nurseries with thousands of genotypes in single-row plots are well suited to capitalize on high throughput phenotyping. Nevertheless, methods to monitor the intrinsically hard-to-phenotype early development of wheat are yet rare. We aimed to develop proxy measures for the rate of plant emergence, the number of tillers, and the beginning of stem elongation using drone-based imagery. We used RGB images (ground sampling distance of 3 mm pixel-1) acquired by repeated flights (≥ 2 flights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…Where higher-resolution imagery is available, for example, either from in-field buggies [ 46 ] or UAV, it becomes possible to undertake more sophisticated image analysis to identify individual plants [ 101 , 102 ], leaves [ 103 ], tillers [ 104 ], or even wheat heads [ 105 , 106 ]. This opens up a wide range of phenotyping possibilities that include selection for characters such as ear density and inflorescence size.…”
Section: Sensing Technologiesmentioning
confidence: 99%
“…Where higher-resolution imagery is available, for example, either from in-field buggies [ 46 ] or UAV, it becomes possible to undertake more sophisticated image analysis to identify individual plants [ 101 , 102 ], leaves [ 103 ], tillers [ 104 ], or even wheat heads [ 105 , 106 ]. This opens up a wide range of phenotyping possibilities that include selection for characters such as ear density and inflorescence size.…”
Section: Sensing Technologiesmentioning
confidence: 99%
“…As an independent random measurement errors was assumed, the parameter σ was fixed to the well-known measurement error of Structure-from-Motion based height estimations (Roth et al, 2020), herein the simulation input σ m (Table 1). Parameters were optimized using the method L-BFGS-B of the base R function optim .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, they found that the model parameters and GLAI dynamics were highly heritable (0.65 ≤ H 2 ≤ 0.98). Similarly, Roth et al (2020) estimated the beginning of stem elongation, the rate of plant emergence, and the number of tillers of wheat seedlings by SVM and crop modelling based on timeseries multi-view angle UAS RGB images at an altitude of 18 m, achieving a tiller number estimation accuracy of R 2 = 0.86. Ubbens et al (2020) proposed the latent space phenotype (LSP) to evaluate time-course phenotypic changes caused by abiotic stress factors, such as drought, nitrogen deficiency, and salinity.…”
Section: Model-assisted Phenotypingmentioning
confidence: 99%